You have the microbiome you deserve. (27th August 2020) - Hill, Colin
ABSTRACT: The human microbiome is one of the most exciting areas of microbiology. From a starting point of tens of papers annually a couple of decades ago, there are now thousands of papers published every year on the microbiome. Huge strides have been made in terms of defining the individual members of complex human microbiomes from different body sites. The individuality and diversity of the human microbiome almost surpasses our ability to comprehend it. Advances in metagenomics and computational sciences have increased the complexity of the field, while at the same time we have moved from regarding the human microbiome as a benign passenger to a situation where it has been linked to almost every chronic disease, including obesity, cancer and infectious disease. The microbiome tantalizes us with the promise of novel therapeutic molecules and modalities for a range of intractable diseases. And yet, very few microbiome-based therapies have made it to the clinic or the pharmacy and we still cannot really define a healthy microbiome. We are entering the most exciting phase of microbiome research, as we develop effective, evidence-based interventions to preserve and restore human health. But we need rigour and numeracy if we are to realize this vision.